2000
DOI: 10.1016/s0304-3959(00)00244-x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc in the extracellular area of the central nervous system is necessary for the development of kainic acid-induced persistent hyperalgesia in mice

Abstract: Kainic acid produces a persistent hyperalgesia when injected intraperitoneally (i.p.) in the rat or mouse. At higher doses than those needed to influence nociception, kainic acid induces seizures and translocation of histologically reactive zinc in the hippocampus. We tested the hypothesis that zinc, localized in a population of small diameter primary afferent neurons, plays a role in kainic acid-induced hyperalgesia similar to that in the hippocampus where zinc translocation accompanies kainic acid-induced se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Mayer et al (1989) showed that Zn 2+ is released simultaneously with glutamate, exerting the effect of a noncompetitive N‐methyl‐D‐aspartate (NMDA) antagonist, and Mayer and Vyklicky (1989) showed that Zn 2+ does not prevent the NMDA binding site affinity or glycine binding on the NMDA receptor. Zn 2+ also inhibits AMPA and intrathecal Zn 2+ in mice and produces an antinociceptive effect but no change in the thermoalgezic tests (Bresink et al, 1996; Larson et al, 2000). Animal studies also showed that Zn 2+ chelators induce hyperalgesia, that Zn 2+ ions have antinociceptive roles in neuropathic pain, and that modulation of Zn 2+ biological fraction induces analgesia (Liu et al, 1999; Larson et al, 2000; Rodriguez‐Munoz et al, 2011).…”
mentioning
confidence: 99%
“…Mayer et al (1989) showed that Zn 2+ is released simultaneously with glutamate, exerting the effect of a noncompetitive N‐methyl‐D‐aspartate (NMDA) antagonist, and Mayer and Vyklicky (1989) showed that Zn 2+ does not prevent the NMDA binding site affinity or glycine binding on the NMDA receptor. Zn 2+ also inhibits AMPA and intrathecal Zn 2+ in mice and produces an antinociceptive effect but no change in the thermoalgezic tests (Bresink et al, 1996; Larson et al, 2000). Animal studies also showed that Zn 2+ chelators induce hyperalgesia, that Zn 2+ ions have antinociceptive roles in neuropathic pain, and that modulation of Zn 2+ biological fraction induces analgesia (Liu et al, 1999; Larson et al, 2000; Rodriguez‐Munoz et al, 2011).…”
mentioning
confidence: 99%
“…A recent study on the spinal cord showed that Zn 2+ might contribute to the modulation of the NMDA receptor-mediated spinal LTP, too (Ma and Zhao 2001). Furthermore, Zn 2+ reduced inflammatory or neuropathic hyperalgesia, a function which was possibly mediated by inhibiting NMDA receptors or by altering the conformation of nerve growth factor (NGF) in the spinal dorsal horn (Safieh-Garabedian et al 1996;Kitto 1997, 1999;Liu et al 1999;Larson et al 2000). Evidence thus exists that the inhibitory effect of Zn 2+ on NMDA receptors may occur also in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc appears to influence pain perception. Thus, in the rat, zinc ions have been found to alleviate thermal hyperalgesia caused by partial nerve injury (Liu et al 1999) or peripheral inflammation (Safieh-Garabedian et al 1996) while chelation with CaEDTA induced peripheral hyperalgesia (Larson and Kitto 1997;Larson et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that transition metal ions such as Fe(II)/(III), Cu(II), Zn(II), Co(II) and Ni(II) etc., can bind to protein molecules to stabilize their structure and play a critical role in modulating physiological functions [1][2][3][4][5][6][7] . Iron, an essential constituent of proteins involved in many cellular processes, is crucial for the growth and viability of almost all organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Since iron is only regulated by uptake 6 , iron chelators have been introduced into clinical practice to protect patients from toxicity caused by iron overload. Various chelators such as cell-impermeable chelators like ethylenediaminetetraacetic acid (EDTA), dipicolinic acid (DPA), diethylenetriaminepentaacetic acid (DTPA) 16 , cell-permeable chelators of hydroxypyridiones such as b-[N-(3-hydroxy-4-pyridone)]-a-aminopropionic acid (L-mimosine) 17 , catecholates such as 1,5,10-N, N', N'-tris (5-sulfo-2,3-dihydroxybenzoyl) triazadecane (3, 6 , and pyrophosphates 6 have been widely studied, although (salts of) EDTA (Fig. 1A) and to a lesser extent DTPA (Fig.…”
Section: Introductionmentioning
confidence: 99%